2016
DOI: 10.1016/j.carbon.2015.10.096
|View full text |Cite
|
Sign up to set email alerts
|

Plasticization for melt viscosity reduction of melt processable carbon fiber precursor

Abstract: Fibers of polyacrylonitrile (PAN), or commonly referred to as acrylic fibers, are found to have many applications. Acrylic fibers are used as a textile medium for high quality and high performance yarns and fabrics, and also as the main supply of precursors for carbon fibers. The main reason of its use as carbon fiber precursor is that the polymer gives high mechanical properties with high carbon yield compared to other polymers. However, a major issue with current carbon fiber production from PAN is the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 28 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…According to the literature, despite the fact that chemical modifications of lignin have been investigated [24], there are no references of successful melt-spun lignin conjugation with high molecular weight commercial spinnable polymers, using esterification after a chlorination reaction, so as to enhance the intermolecular bonds between the compounds. The successful chemical synthesis, which was conducted in this study without the use of plasticization [66] and confirmed by characterization, provided thermal process ability to the precursor fiber. Anthracene-oil-derived pitches as precursors have led to green carbon fibers [67], but the diameter of the fibers varied depending on the winding speed, and overall, that method was more expensive than using lignin in the blends.…”
Section: Appendix a Thermal Expansion Of The Gfrp Compositementioning
confidence: 62%
“…According to the literature, despite the fact that chemical modifications of lignin have been investigated [24], there are no references of successful melt-spun lignin conjugation with high molecular weight commercial spinnable polymers, using esterification after a chlorination reaction, so as to enhance the intermolecular bonds between the compounds. The successful chemical synthesis, which was conducted in this study without the use of plasticization [66] and confirmed by characterization, provided thermal process ability to the precursor fiber. Anthracene-oil-derived pitches as precursors have led to green carbon fibers [67], but the diameter of the fibers varied depending on the winding speed, and overall, that method was more expensive than using lignin in the blends.…”
Section: Appendix a Thermal Expansion Of The Gfrp Compositementioning
confidence: 62%
“…According to the literature, despite the fact that chemical modifications of lignin have been investigated [24], there are no references of successful melt-spun lignin conjugation with high molecular weight commercial spinnable polymers, using esterification after a chlorination reaction, so as to enhance the intermolecular bonds between the compounds. The successful chemical synthesis, which was conducted in this study without the use of plasticization [66] and confirmed by characterization, provided thermal process ability to the precursor fiber. Anthracene-oil-derived pitches as precursors have led to green carbon fibers [67], but the diameter of the fibers varied depending on the winding speed, and overall, that method was more expensive than using lignin in the blends.…”
Section: Outcome Analysismentioning
confidence: 62%
“…Considering the melt-processability, a precursor with a liquid-like behavior and low viscosity at the processing temperature is typically favorable . Although a higher processing temperature would lower the viscosity of the CF precursor facilitating fiber spinning, a crosslinking reaction is expected as well due to the thermal-induced polycondensation between PAH side groups.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the melt-processability, a precursor with a liquid-like behavior and low viscosity at the processing temperature is typically favorable. 55 Although a higher processing temperature would lower the viscosity of the CF precursor facilitating fiber spinning, a crosslinking reaction is expected as well due to the thermal-induced polycondensation between PAH side groups. Since the crosslinking reaction lowers the melt-processibility, the undesirable chemical reactions prior to the carbonization step need to be minimized under well-defined process conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%